The Genealogy of the Austrian School of Economics - Chavez Salazar, Nelson David (2018)
This work aims to briefly present the genesis and historical evolution of the Austrian School of Economics and to formulate a series of considerations about the future of its research program as well. In order to develop the historical report, we will use the typology proposed by the British economist Israel Kirzner - one of the greatest exponents of the Austrian tradition - that distinguishes four stages in the development of this line of economic thought. The Austrian paradigm is a deep and systematic analysis of human nature and the relation between the individual and society. It brings the importance for the global economic thinking and the urgency of applying its approaches to the contemporary world.